2018
DOI: 10.1021/acsami.8b04373
|View full text |Cite
|
Sign up to set email alerts
|

Control of Integrin Affinity by Confining RGD Peptides on Fluorescent Carbon Nanotubes

Abstract: Integrins are transmembrane receptors that mediate cell-adhesion, signaling cascades and platelet-mediated blood clotting. Most integrins bind to the common short peptide Arg-Gly-Asp (RGD). The conformational freedom of the RGD motif determines how strong and to which integrins it binds. Here, we present a novel approach to tune binding constants by confining RGD peptide motifs via noncovalent adsorption of single-stranded DNA (ssDNA) anchors onto single-walled carbon nanotubes (SWCNTs). Semiconducting SWCNTs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 68 publications
(110 reference statements)
0
43
0
6
Order By: Relevance
“…Another factor affecting cell adhesion is the available surface concentration of integrin ligands 21,36 . By using approaches from nanotechnology it is possible to control the exact distance and overall density of integrin ligands such as RGD and the Mac-1 ligand GPB1 or even link them to advanced near infrared fluorescent nanomaterials 27,42,43 . For neutrophils it has been shown that adhesion maturation and cellular functions such as spreading and migration depend on ligand density 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Another factor affecting cell adhesion is the available surface concentration of integrin ligands 21,36 . By using approaches from nanotechnology it is possible to control the exact distance and overall density of integrin ligands such as RGD and the Mac-1 ligand GPB1 or even link them to advanced near infrared fluorescent nanomaterials 27,42,43 . For neutrophils it has been shown that adhesion maturation and cellular functions such as spreading and migration depend on ligand density 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Durch die große Verfügbarkeit von transgenen Organismen und Zellen mit GFP‐Fusionsproteinen ist GFP ist ein sehr vielseitiges Zielmolekül. Um die nIR‐Fluoreszenz der SWCNTs nicht zu zerstören, verwenden wir eine nicht‐kovalente Funktionalisierungsstrategie, obwohl Setaro et al. kürzlich auch eine kovalente Funktionalisierungsstrategie unter Erhaltung der nIR‐Fluoreszenz beschrieben haben .…”
Section: Figureunclassified
“…nIR fluorescent nanomaterials include InAs quantum dots, lanthanide doped nanoparticles or semiconducting single-walled carbon nanotubes (SWCNTs) [8][9][10][11][12] . For example, SWCNTs have been used as building blocks for nIR imaging and as fluorescent sensors that detect small signaling molecules, proteins or lipids [13][14][15][16][17][18][19] . They can be chemically tailored and have been used to reveal spatiotemporal release patterns of neurotransmitters from single cells 2,15,[20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, SWCNTs have been used as building blocks for nIR imaging and as fluorescent sensors that detect small signaling molecules, proteins or lipids [13][14][15][16][17][18][19] . They can be chemically tailored and have been used to reveal spatiotemporal release patterns of neurotransmitters from single cells 2,15,[20][21][22] . However, most nIR fluorescent nanomaterials often have low quantum yields, lack biocompatibility or are restricted to certain emission/excitation wavelengths.…”
Section: Introductionmentioning
confidence: 99%